Baseline associations of cardiometabolic risk factors, executive function, and white matter microstructure in the DIRECT‐PLUS trial. (December 2021) - Kaplan, Alon; Beyer, Frauke; Witte, A. Veronica; Shai, Iris
Abstract: Background: Cardiometabolic risk factors including mid‐life obesity, diabetes and hypertension are associated with accelerated cognitive decline, e.g. in executive function, and brain aging, e.g. alterations in white matter (WM) microstructure [1]. Method: 290 participants (34 females, mean age= 49 y (30 – 79 y) of the DIRECT‐PLUS trial (clinicaltrials.gov ID: NCT03020186, [2]) participated in diffusion‐weighted imaging on a 3T Philips. Tract‐based spatial statistics provided hemisphere‐averaged fractional anisotropy (FA) of 9 fiber tracts (genu/body of corpus callosum, body and crus of fornix, (hippocampal) cingulum, inferior/superior longitudinal fasciculus (i/sLF) and uncinate fasciculus. We tested the association of age, sex, five risk factors (body mass index (BMI), systolic blood pressure (SBP), glycated hemoglobin, high and low‐density lipoprotein), four measures of executive function from the brief executive function battery and average FA of these WM tracts with correlations and linear regression models, adjusting for age and sex, in R version 3.6.1, corrected for multiple testing using false discovery rate (FDR). Result: Age was associated with lower FA in the cingulum (r=‐0.56, p<0.001), uncinate fasciculus (r=‐0.51, p<0.001), hippocampus cingulum (r=‐0.39, p<0.001), iLF (‐0.19, p=0.001) and sLF (r=‐0.18, p=0.001). FA in the fornix, hippocampus cingulum and iLF were higher in men as compared to women (p<0.05 for all). Among cardiometabolic risk factors, higher BMI was associated with significantly lower FA in iILF (β = ‐0.002, p=0.0009, padj=0.035), and higher SBP was associated with lower FA in uncinate fasciculus (β= ‐0.0006, p=0.0012, padj=0.035)None of the executive function measures was significantly related to FA of WM tracts after adjusting for age and sex and controlling for FDR. Conclusion: Our findings corroborate previous findings of the adverse impacts of cardiometabolic risk on WM microstructure. Upcoming longitudinal investigations in this dataset will show whether improved cardiometabolic function, induced by a dietary intervention, will modify the trajectories of WM microstructure and cognitive performance. Figure 1: Higher BMI and higher SBP were significantly associated with lower FA in two major WM tracts (blue: ILF, green: uncinate fasciculus)[1] Wassenaar, TM., et al. NBA (2019) [2] Tsaban, G, et al. Heart (2020).